Characteristics of Exercise Training Interventions to Improve Cardiorespiratory Fitness After Stroke: A Systematic Review With Meta-analysis. (November 2013) - Marsden, Dianne L.; Dunn, Ashlee; Callister, Robin; Levi, Christopher R.; Spratt, Neil J.
Background . Cardiorespiratory fitness is low after stroke. Improving fitness has the potential to improve function and reduce secondary cardiovascular events. Objective . This review with meta-analysis aims to identify characteristics and determine the effectiveness of interventions to improve cardiorespiratory fitness after stroke. Methods . A systematic search and review with meta-analysis was undertaken. Key inclusion criteria were the following: peer-reviewed articles published in English, adult stroke survivors, an intervention with the potential to improve cardiorespiratory fitness, and peak oxygen consumption (VO2peak ) assessed preintervention and postintervention via a progressive aerobic exercise test. Results . From 3209 citations identified, 28 studies were included, reporting results for 920 participants. Studies typically included chronic, ambulant participants with mild to moderate deficits; used an aerobic or mixed (with an aerobic component) intervention; and prescribed 3 sessions per week for 30 to 60 minutes per session at a given intensity. Baseline VO2peak values were low (8-23 mL/kg/min). Meta-analysis of the 12 randomized controlled trials demonstrated overall improvements in VO2peak of 2.27 (95% confidence interval = 1.58, 2.95) mL/kg/min postintervention. A similar 10% to 15% improvement occurred with both aerobic and mixed interventions and in shorter (≤3 months) and longer (>3 months) length programs. Only 1 study calculated total dose received and only 1 included long-term follow-up. Conclusions . The results demonstrate that interventions with an aerobic component can improve cardiorespiratory fitness poststroke. Further investigation is required to determine effectiveness in those with greater impairment and comorbidities, optimal timing and dose of intervention, whether improvements can be maintained in the longer term, and whether improved fitness results in better function and reduced risk of subsequent cardiovascular events.